Transfer of the Full-Length Dystrophin-Coding Sequence into Muscle Cells by a Dual High-Capacity Hybrid Viral Vector with Site-Specific Integration Ability - Gonçalves, Manuel A. F. V. (American Society for Microbiology, 2005)
Duchenne muscular dystrophy (DMD) is caused by mutations in the DMD gene, making it a potential target for gene therapy. There is, however, a scarcity of vectors that can accommodate the 14-kb DMD cDNA and permanently genetically correct muscle tissue in vivo or proliferating myogenic progenitors in vitro for use in autologous transplantation. Here, a dual high-capacity adenovirus-adeno-associated virus (hcAd/AAV) vector with two full-length human dystrophin-coding sequences flanked by AAV integration-enhancing elements is presented. These vectors are generated from input linear monomeric DNA molecules consisting of the Ad origin of replication and packaging signal followed by the recently identified AAV DNA integration efficiency element (p5IEE), the transgene(s) of interest, and the AAV inverted terminal repeat (ITR). After infection of producer cells with a helper Ad vector, the Ad DNA replication machinery, in concert with the AAV ITR-dependent dimerization, leads to the assembly of vector genomes with a tail-to-tail configuration that are efficiently amplified and packaged into Ad capsids. These dual hcAd/AAV hybrid vectors were used to express the dystrophin-coding sequence in rat cardiomyocytes in vitro and to restore dystrophin synthesis in the muscle tissues of mdx mice in vivo. Introduction into human cells of chimeric genomes, which contain a structure reminiscent of AAV proviral DNA, resulted in AAV Rep-dependent targeted DNA integration into the AAVS1 locus on chromosome 19. Dual hcAd/AAV hybrid vectors may thus be particularly useful to develop safe treatment modalities for diseases such as DMD that rely on efficient transfer and stable expression of large genes.